QR-Barcode Application for Barrier Gate Opener based on Android - Merdana, Okta (International Journal of Computer, Network Security and Information System, 2020)
The use of Android-based smartphones is a personal assistant who is often a primary need in helping human activities. Based on this, this study uses Android to create a control device for access rights using QR-Code to open the barrier gate where the data will be added to the database server, and the system is called Q-BaGOS (QR-Code Based Barrier Gate Opening System). The design of this access system utilizes a QR-code scanner application that is made in-house and modified with coding to instruct Android as a medium to open a barrier gate containing a QR-code. In the application, there are menus such as login username and password, status and barcode data. If you already have user data, it can be used as an access right to unlock the barrier gate. In this case, to manage it all, a web server is built that will communicate with Arduino Uno to control the entire security system, by storing user access rights data, recording user data that performs scanners and entering the port. Barcode or barcode is a set of data that is described by lines and spacing (space). The working principle of this tool when opening a scanner application on Android, users are required to log in the username and password data first. After logging in, it automatically opens the QR-code scanner camera. After the scan process automatically enters the data on the web database server, then the servo door automatically opens. After the user enters, the ultrasonic sensor works, and the barrier gate is automatically closed again